Calibration Estimation under Non-response and Missing Values in Auxiliary Information - Thomas Laitila; Lisha Wang (Örebro University School of Business, 2015)
The calibration approach is suggested in the literature for estimation in sample surveys under non-response given access to suitable auxiliary information. However, missing values in auxiliary information come up as a thorny but realistic problem. This paper considers the consistency of the calibration estimator suggested by Särndal & Lundström (2005)for estimation under nonresponse, connected with how imputation of auxiliary information based on different levels of register information affects the calibration estimator. An illustration is given with results from a small simulation study.
Keywords: C42; C83; 330; Sample survey; non-response; imputation; consistency; bias